Semantic Relations of Papuan Indonesian Dialect - Juana Juvita; Farida Maricar; Sunaedin Ode Mulae (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
This study aims to investigate semantic meanings which include lexical relations and meaning properties in Papuan Indonesian dialect. It used natural data obtained in conversations among 6 Papuan students who studied at Khairun University. These participants were selected purposively considering the variety of their ethnicities and their membership in Papuan students’ community. The data were collected in three steps: interview, observation, and documentation. The data were then analysed qualitatively to elicit the dominant semantic meanings in the utterances. There are two lexical relations identified: synonymy and polysemy. The synonyms in the Papuan Indonesian dialect are influenced by the intensity of use in society, taken from other language terms, and the description of the meaning of the word. For meaning properties, two types are found: ambiguity and redundancy. The Papuan Indonesian dialect contains a lot of redundancy, that is, the use of particle language in terms of semantics does not make a difference in meaning. This study also found that based on its semantic relations, Papuan Indonesian dialect is also influenced by several factors, namely: (1) administrative unity; (2) similarity in geographical area; (3) special community identity; and (4) historical experience.